Data on the annual home range of Charlevoix caribou - Leblond, Mathieu; Dussault, Christian; Ouellet, Jean-Pierre (Dryad Digital Repository, 2013)
Description of the home range data collected using VHF telemetry from 1999-2000, and GPS telemetry from 2004-2011, on 87 forest-dwelling caribou in the Charlevoix region of Québec, Canada. Each row corresponds to one annual home range (one individual-year). Included are data on individuals (ID, sex, age, type of collar); telemetry program (year, start- and end-dates of monitoring, and duration); status of individuals for the broad scale survival analysis (whether individuals died [1=died], and of which cause [1=predation, 2=natural, 4=undetermined]); information on reproductive success of females from 2004-2007 (whether females had a calf [1=calved], and whether he survived through its first year of life [1=survived]); information on space use (home range size and mean movement rate); and finally home range composition (active, derelict, and total road density, and percentage of each habitat class).